Implementation of Thematic Learning Media Using Camtasia Studio 8 to Improve Student Learning Outcomes in Elementary School - Nana Supriyatna (Universitas Sebelas Maret, 2020)
This research is a classroom action research which consists of two cycles. This classroom action research has two cycles in one cycle, there are four stages, namely planning, implementing, observing and reflecting. The research subjects were students of grade V SDN Majingklak 03 Wanareja, Central Java with a total of 29 students. Data collection techniques using test and non-test techniques. The assessment instrument uses item items and observations of the scoring rubric. Analysis of the data used in the study included a comparative descriptive technique, namely a statistical technique by comparing the scores between cycles, the mean, the minimum score, the maximum, and the percentage. The results of the study that the use of video Camtasia Studio 8 media can improve student learning outcomes in the theme of 4 Healthy is Important of Class V SDN Majingklak 03 Wanareja. 28%, while students who completed were 21 out of 29 students or 72%. In the second cycle, in the initial conditions according to the background of the research, there were 8 students out of 29 students who had not completed it or 28%. In cycle II, there were 7 out of 29 students or 24% of the students who had not completed, while 22 out of 29 students or 76% of the students who had completed were. This means that student learning outcomes increase from cycle I to cycle II.